Identification and Characterization of Market Garden Crops Grown Near Landfills in Abidjan District - , Harding Charlemagne Assy; , Ghislaine Chépo Dan; , Désiré Yapi Assoi Yapi; , Ohouo Régina Antoinette Don (Archives of Current Research International, 2024)
Abstract: Market garden crops constitutes an important source of food and is one of the most income-generating activities in Côte d'Ivoire. In the Abidjan district, several market gardening sites are located near illegal landfill sites, therefore representing a danger for consumers. Aims: This study was carried out to map these different sites, inventory the plant species cultivated and characterize the cultivation practices with a view to highlighting the constraints and identifying prospects for improvement. Methodology: Semi-structured individual interviews were carried out in 4 communes of Abidjan (Abobo, Bingerville, Cocody and Port-bouët) to collect information from 400 residents including 280 men and 120 women. The statistical analysis of the survey results was carried out using Google Form and Excel software. Results: The results revealed six (6) market garden sites with landfills distributed in four (4) different communes (Abobo - Akeikoi village; Bingerville - Bingerack city; Cocody - M'pouto village and M'badon village; Port-bouët - 4th bima and Mafiblé village). Thirteen (13) market garden species which are divided into eight families. Lettuce and basil are grown on all identified sites and represent the most cultivated species (40%). Market garden crops is practiced by young people aged 10 to 30 (70%) with a relatively low level of education. Pests (insects, rodents, fungi) and heavy metals from illegal dumps constitute the main obstacles to production and are vectors of frequent diseases. Conclusion: It would be wise to adopt an integration policy for market gardening, in urban development plans, and to combat the proliferation of uncontrolled landfill sites, this will help to improve the quality and yield of market garden crops in Abidjan.